Biocompatibility of Ti-48Al-2Cr-2Nb produced by electron beam powder bed fusion (EB-PBF). (2022) - Galati, Manuela; Gatto, Maria Laura; Bloise, Nora; Fassina, Lorenzo; Saboori, Abdollah; Visai, Livia; Mengucci, Paolo; Iuliano, Luca
Abstract: Ti-48Al-2Cr-2Nb is a well-known material for fabricating bulky parts using the electron beam powder bed fusion process. This work investigates the biocompatibility of this material as an alternative to the most common titanium alloys, which contain toxic elements such as Vanadium. The viability and proliferation of NIH-3T3 fibroblasts on Ti-48Al-2Cr-2Nb scaffolds are investigated. The in vitro viability tests are performed after incubation for 1, 4 and 7 days.